2013
DOI: 10.1364/oe.21.011482
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature stability and selective thermal emission of polycrystalline tantalum photonic crystals

Abstract: We present the results of extensive characterization of selective emitters at high temperatures, including thermal emission measurements and thermal stability testing at 1000 °C for 1h and 900 °C for up to 144 h. The selective emitters were fabricated as 2D photonic crystals (PhCs) on polycrystalline tantalum (Ta), targeting large-area applications in solid-state heat-to-electricity conversion. We characterized spectral emission as a function of temperature, observing very good selectivity of the emission as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(124 citation statements)
references
References 26 publications
4
118
0
2
Order By: Relevance
“…However, thermal emission tailoring at elevated temperatures (>1000K) remains exceedingly difficult [14][15][16][17][18] . Here, we address this challenge by coupling the hot emitter with a cold-side nanophotonic interference system.…”
Section: Radiation From Very Hot Objects (Such As the Sun And Incandementioning
confidence: 99%
“…However, thermal emission tailoring at elevated temperatures (>1000K) remains exceedingly difficult [14][15][16][17][18] . Here, we address this challenge by coupling the hot emitter with a cold-side nanophotonic interference system.…”
Section: Radiation From Very Hot Objects (Such As the Sun And Incandementioning
confidence: 99%
“…For plasmonic absorbers and 2D or 3D PhCs, the slightly higher thermal emittance decreases their thermal transfer efficiencies at high temperatures. It is also relatively more challenging to fabricate plasmonic absorbers and 2D or 3D PhCs that are durable for high temperature operations [33,34]. Other types of selective solar absorbers that have been previously considered in the literature, but are not explored here in detail, include textured absorbers [35][36][37][38] and intrinsic absorber materials [36,[38][39][40].…”
Section: Selective Solar Absorbermentioning
confidence: 99%
“…Experiments have shown that nano-and microstructures degrade under high temperature exposure for long times [148][149][150][151]. Different mechanisms can lead to such degradation, including chemical reactions [33,70,150], recrystallization [34,148] and surface diffusion [152,153]. These structural degradation processes could eventually remove the fine features of the structure.…”
Section: Packaging For Commercial Deploymentmentioning
confidence: 99%
“…1 Several materials have been proposed for selective emission, including plasmonic metamaterials, 2-4 refractory plasmonic structures, 5 rare earth materials, [6][7][8] and photonic crystals (PhCs). [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] However, realistic selective emitters still have residual low energy emission near the bandgap that can considerably limit the conversion efficiency. Significant improvement can be achieved by the use of cold-side PhC filters, including plasma filters, quarter-wave stacks, 25 and rugate filters.…”
Section: Introductionmentioning
confidence: 99%
“…40 Further, the IPSE is relatively amenable to fabrication in the near term, with key features already achieved in previous experimental work. [20][21][22]25,26 2 Design of the Integrated Photonic Crystal Selective Emitter…”
Section: Introductionmentioning
confidence: 99%